Online video advertising - Bowman, Tom (Henry Stewart Talks, 2009)
The state of the market, The advent of new video content and critical changes in consumer behavior, What is possible today, Current advertising possibilities and limitations, Opportunities, User insights, Campaign management, pricing, standards and specifications
Archived at 2022/04/11